1996
DOI: 10.3109/10428199609054843
|View full text |Cite
|
Sign up to set email alerts
|

c-Myc and Bcl-2 Protein Expression During the Induction of Apoptosis and Differentiation in TNFα-Treated HL-60 Cells

Abstract: We examined c-Myc and Bcl-2 protein expressions during the induction of apoptosis and differentiation in TNF alpha-treated HL-60 cells using a two-color flow cytometric method. We found that c-Myc protein was rapidly down-regulated in the apoptotic cells while Bcl-2 protein was expressed at relatively high levels. Concomitantly with terminal differentiation Bcl-2 protein was down-regulated in differentiating cells as well as c-Myc protein. We also showed that c-myc antisense oligonucleotides could induce apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Regulation of the relative levels of Bcl-2 and c-Myc may play an important role in modulating the susceptibility of cells to differentiation (Li et al, 2004;Wu et al, 2002). Previous studies have demonstrated that HL-60 cells exhibited an overexpression of Bcl-2 and c-Myc proto-oncogene and that alteration of cellular oncogenes occur during the differentiation of HL-60 cells (Kumakura et al, 1996). Within myeloid lineage, Bcl-2 is over-expressed in early myeloid precursors but under-expressed or absent in matured myeloid cells and neutrophils (Gazitt et al, 2001;Blagosklonny et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulation of the relative levels of Bcl-2 and c-Myc may play an important role in modulating the susceptibility of cells to differentiation (Li et al, 2004;Wu et al, 2002). Previous studies have demonstrated that HL-60 cells exhibited an overexpression of Bcl-2 and c-Myc proto-oncogene and that alteration of cellular oncogenes occur during the differentiation of HL-60 cells (Kumakura et al, 1996). Within myeloid lineage, Bcl-2 is over-expressed in early myeloid precursors but under-expressed or absent in matured myeloid cells and neutrophils (Gazitt et al, 2001;Blagosklonny et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Differentiation of HL-60 is induced into granulocytes by dimethyl sulfoxide (DMSO) and all-trans retinoic acid (ATRA), and into monocytic-like cells by phorbol ester (TPA) and 1,25-dihydroxy-vitamin D3 (Tsiftsoglou et al, 2003). In HL-60 cells, differentiation is induce-specific and is characterized by agents to differentiated is a marked increase in the proportion of G0/G1 cells (Yen et al, 2006), and the modulation of cyclin/CDK (Horie et al, 2004;Wang et al, 1996;Barrera et al, 2004;Pizzimenti et al, 1999;Kumakura et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Concomitant down-regulation of c-MYC and BCL-2 are important early events closely associated with cell growth arrest, terminal differentiation and apoptotic death in several cell types [54,55]. In leukemia cells, c-MYC expression decreases within 12 h of RA stimulation and is further down-regulated during differentiation [56].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor-a has been shown to induce cell differentiation in several leukemic cell lines including HL-60, U937, and WEHI-3B JCS [9,[21][22][23]. Furthermore, it has been shown that the differentiation of the human leukemic cells into mature cells is enhanced by the combination of TNF-a and interleukin-4 (IL-4) [9].…”
Section: Tnf-a Increases the Differentiative Efficacy Of Dmso For Hl-mentioning
confidence: 99%